1997
DOI: 10.1038/ki.1997.158
|View full text |Cite
|
Sign up to set email alerts
|

Dietary antioxidant inhibits lipoprotein oxidation and renal injury in experimental focal segmental glomerulosclerosis

Abstract: Lipid peroxidation may be involved in the pathogenesis of focal segmental glomerulosclerosis (FSGS). In the present study we examined whether lipid-soluble antioxidants, probucol and vitamin E, could inhibit renal injury in rats with chronic puromycin aminonucleoside (PA) nephrosis and dietary hypercholesterolemia by protecting lipoproteins from oxidation. Male Sprague-Dawley rats received six intraperitoneal injections of PA over a 10 week period and were fed a high cholesterol (HC) diet (PA-HC) or the same d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 42 publications
3
53
0
1
Order By: Relevance
“…Several lines of evidence indicate that oxidant stress is a pathogenic factor in lipid-induced nephropathy. By immunohistology, oxidatively modifi ed lipoproteins were demonstrated in focal segmental glomerulosclerosis in rat and humans (57)(58)(59). However, the steps leading to oxidative modifi cation of proteins and lipoproteins have not been elucidated in detail yet.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that oxidant stress is a pathogenic factor in lipid-induced nephropathy. By immunohistology, oxidatively modifi ed lipoproteins were demonstrated in focal segmental glomerulosclerosis in rat and humans (57)(58)(59). However, the steps leading to oxidative modifi cation of proteins and lipoproteins have not been elucidated in detail yet.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, vitamin E attenuates chronic injury associated with glomerulosclerosis (18) or aging (19), and prevents renal interstitial fibrosis associated with HC (20). We have previously shown that combined administration of vitamins E and C in experimental HC reduced LDL oxidizability and preserved renal endothelial function (9).…”
mentioning
confidence: 99%
“…Similarly, we have shown that this condition can induce functional vascular changes in the kidney, both in vivo and in vitro (50), which precede the onset of overt atherosclerotic lesions (10,20,42). Subsequently, HC subjects may develop glomerulosclerosis (24), ox-LDL deposition (35,36), and chronic tubulointerstitial damage (25). Increased oxidative stress appears to be one of the main pathogenic mechanisms mediating lipid-induced nephropathy, and involves increased generation of ROS, decreased NO bioavailability, and consequently endothelial dysfunction, a condition characterized by a blunted endotheliumdependent vasodilator response.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, HC has been demonstrated to be an independent risk factor for the onset (10) and progression (22) of renal disease and can both induce and worsen renal glomerular, interstitial, and vascular damage (30,35). We have previously shown (11,20,42) that even a short exposure to diet-induced HC is associated with increased formation of oxidized LDL (ox-LDL) and reactive oxygen species (ROS).…”
mentioning
confidence: 99%